Therapeutic effects of Buyang Huanwu Tang combined with RT-PA intravenous thrombolysis on stroke of Qi deficiency and blood stasis type and its impact on Keap1-Nrf2/ARE pathway antioxidant stress: Buyang Huanwu Tang and RT-PA in Qi deficiency stroke - Liang, Shunli; Wu, You; Zhang, Rongbo; Xin, Xilin; Xu, Linsheng (Cellular and Molecular Biology, 2023)
This study investigated the impact of combining traditional Chinese medicine, Buyang Huanwu Tang, with intravenous thrombolysis using alteplase (rt-PA) in treating ischemic stroke patients with qi deficiency and blood stasis. A single-center clinical randomized trial involved 117 ischemic stroke patients treated with rt-PA in the neurology department from January 2019 to December 2021. Patients were randomly divided into two groups: the control group (58 patients) received rt-PA alone, while the combined group (59 patients) received rt-PA along with Buyang Huanwu Tang. Neurological deficit scores (NIHSS) were assessed before and after treatment, along with hemorheological indicators, vascular endothelial growth factor (VEGF), matrix metalloproteinase-9 (MMP-9), and Keap1-Nrf2/ARE pathway oxidative stress indicators (Keap1, Nrf2, ARE, and NQO1 proteins). Before treatment, there were no significant differences between the groups. After treatment, the combination group exhibited lower NIHSS scores at 4, 8, and 12 weeks, indicating significant improvement compared to the control group. Additionally, the combination group demonstrated reduced plasma viscosity, low and high shear viscosity, and improved red blood cell aggregation compared to the control group after 8 weeks of treatment. Furthermore, the combination group showed elevated MMP-9 levels and reduced VEGF levels, suggesting favorable outcomes. Regarding the Keap1-Nrf2/ARE pathway, Nrf2 and NQO1 protein expression levels were higher in the combination group after 8 weeks of treatment. Clinical efficacy assessment revealed that the combined treatment group had a significantly better overall treatment response. In conclusion, combining Buyang Huanwu Tang with rt-PA intravenous thrombolysis effectively mitigated oxidative stress damage in the Keap1-Nrf2/ARE pathway among ischemic stroke patients with qi deficiency and blood stasis. This approach promoted neurological function recovery and improved overall treatment outcomes.